Convergence studies of finite element model for analysis of steel-concrete composite beam using a higher-order beam theory. (October 2020) - Uddin, Md. Alhaz; Alzara, Majed Abdulrahman; Mohammad, Noor; Yosri, Ahmed
Abstract: The finite element model based on a higher-order beam theory (HBT) is the most favourable modelling technique for an accurate prediction response of steel-concrete composite beams. The higher-order beam model is achieved by taking a third-order variation of the longitudinal displacement over the beam depth for the steel and concrete layers separately. The deformable shear studs used for connecting the concrete slab with the steel girder are modelled as distributed shear springs along with the interface between these two material layers. For the implementation of finite element formulation, the field consistent technique and full numerical integration of the stiffness matrix is carried out in order to avoid any shear locking and stress oscillation problem. There are four different types of beam elements incorporated to develop models to observe an optimal number of beam element required for good convergence. The proposed model is assessed through validation and verification using existing published results and numerical results produced by detailed 2D finite element modelling of steel-concrete composite beams. The validation and verification show a very good performance of the proposed finite element models.